Online Strategies Drive Fast Food Consumer Behavior in pandemic marketing: Strategi Online Mendorong Perilaku Konsumen Makanan Cepat Saji dalam pemasaran pandemi - Aulia, Nabilah Syaharani; Adji Kusuma, Kumara (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates how social restrictions, online marketing, and product bundling influence consumer behavior in purchasing McDonald's products in Sidoarjo. Surveying 108 consumers, data were analyzed using SPSS 20 with various statistical tests. Results indicate that social restrictions have a mixed but not significant impact, while online marketing and product bundling both significantly and positively affect consumer behavior. The findings underscore the effectiveness of online marketing and product bundling strategies in engaging consumers and boosting sales during the pandemic. Highlights: 1. Social restrictions: mixed impact, not significant on consumer behavior.2. Online marketing: significant, positive effect on consumer behavior.3. Product bundling: enhances engagement, boosts purchasing decisions. Keywords: Consumer behavior, Social restrictions, Online marketing, Product bundling, Fast food industry